2008
DOI: 10.1093/cercor/bhn188
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Context Enhances Auditory Novelty Processing in Superior Temporal Gyrus

Abstract: Visualizing emotionally loaded pictures intensifies peripheral reflexes toward sudden auditory stimuli, suggesting that the emotional context may potentiate responses elicited by novel events in the acoustic environment. However, psychophysiological results have reported that attentional resources available to sounds become depleted, as attention allocation to emotional pictures increases. These findings have raised the challenging question of whether an emotional context actually enhances or attenuates audito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 58 publications
2
45
1
Order By: Relevance
“…There is compelling evidence that emotion, which as a concept comprises reward, facilitates and potentiates perceptual processes and attention (Bocanegra and Zeelenberg, 2009;Dominguez-Borras et al, 2009;Phelps et al, 2006). In the present paper, processing of rewarding stimuli was associated with a higher connectivity of the IC1, a network involving frontal and occipital areas.…”
Section: Discussionmentioning
confidence: 47%
“…There is compelling evidence that emotion, which as a concept comprises reward, facilitates and potentiates perceptual processes and attention (Bocanegra and Zeelenberg, 2009;Dominguez-Borras et al, 2009;Phelps et al, 2006). In the present paper, processing of rewarding stimuli was associated with a higher connectivity of the IC1, a network involving frontal and occipital areas.…”
Section: Discussionmentioning
confidence: 47%
“…Auditory responses to right-ear deviants were enhanced during sad mood as compared to neutral mood, reflecting mood-dependent modulation of mismatch responses to consonant-vowel syllables. Previous studies investigating the effect of emotional context on the processing of neutral auditory stimuli reported enhanced acoustic novelty processing for negative valence [20][23]. In a similar vein, dysphoric persons show impaired attention disengagement from negative stimuli [45], [46].…”
Section: Discussionmentioning
confidence: 76%
“…Alexandrov and colleagues [20] created an emotional context by monetary reward or punishment and reported significantly larger auditory cortex event-related potentials in response to negative as compared to positive trials. In an fMRI study by Domínguez-Borràs and colleagues [23], subjects conducted a color decision task embedded in the presentation of facial expressions of negative and neutral valence. In the context of negative expressions, responses to novel sounds in superior temporal gyrus were enhanced as well.…”
Section: Introductionmentioning
confidence: 99%
“…With antidepressant treatment, these activations are normalised (Arnone et al, 2012;Delaveau et al, 2011;Godlewska et al, 2012). Other brain areas implicated in the mood and anxiety disorders are: the insula, linked to self-awareness and autonomic regulation of emotions (Craig, 2009;Paulus and Stein, 2006); the hippocampus, involved in memory formation, learning, sensitivity to context, and regulation of stress, as well as a major site of neurogenesis (Bellani et al, 2010;Brooks et al, 2012;den Heijer et al, 2012); the thalamus, a processing centre for sensation and motor regulation, which also plays a role in awareness, attention, memory, and language (Herrero et al, 2002;Matsumoto et al, 2001); the cingulate cortex, involved in the regulation of both cognitive and emotional processing with functions in directed attention and motivated behaviour (Amiez et al, 2012;Blair et al, 2012;Bush et al, 2000;Etkin et al, 2011); and the superior temporal gyrus (STG), implicated not only in auditory processes, but also in language processing, social cognition, and emotion perception in faces (Bigler et al, 2007;Domínguez-Borràs et al, 2009;Turk-Browne et al, 2010). Furthermore, research on the treatment of affective disorders has demonstrated that treatment restores the function of these regions (e.g., Arce et al, 2007;Korb et al, 2011).…”
Section: Introductionmentioning
confidence: 99%